2022
DOI: 10.1002/mrm.29148
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the capillary level input function for dynamic contrast‐enhanced MRI of the breast using a deep learning approach

Abstract: Purpose: To develop a deep learning approach to estimate the local capillarylevel input function (CIF) for pharmacokinetic model analysis of DCE-MRI. Methods:A deep convolutional network was trained with numerically simulated data to estimate the CIF. The trained network was tested using simulated lesion data and used to estimate voxel-wise CIF for pharmacokinetic model analysis of breast DCE-MRI data using an abbreviated protocol from women with malignant (n = 25) and benign (n = 28) lesions. The estimated pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…31 As an alternative, to improve the uncertainty coming from the AIF selection, we seek to implement deep-learning based DCE analysis, which has recently shown to estimate BBB permeability with reduced scan time. 32,33 Also, our radial imaging sequence allows retrospective selection of temporal resolution, and previous studies have already demonstrated this flexibility for different applications. 9,34 While it is not presented here, we investigated the effect of reconstructing dynamic images at different temporal resolutions and identified the optimal temporal resolution for appropriately selecting AIF and capturing contrast agent dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 As an alternative, to improve the uncertainty coming from the AIF selection, we seek to implement deep-learning based DCE analysis, which has recently shown to estimate BBB permeability with reduced scan time. 32,33 Also, our radial imaging sequence allows retrospective selection of temporal resolution, and previous studies have already demonstrated this flexibility for different applications. 9,34 While it is not presented here, we investigated the effect of reconstructing dynamic images at different temporal resolutions and identified the optimal temporal resolution for appropriately selecting AIF and capturing contrast agent dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…The accurate AIF estimation is essential for accurate parameter estimation and it needs to be carefully examined between 3D UTE‐GRASP method and the conventional sequence, as different undersampling in Cartesian acquisition has shown to degrade the temporal fidelity 31 . As an alternative, to improve the uncertainty coming from the AIF selection, we seek to implement deep‐learning based DCE analysis, which has recently shown to estimate BBB permeability with reduced scan time 32,33 . Also, our radial imaging sequence allows retrospective selection of temporal resolution, and previous studies have already demonstrated this flexibility for different applications 9,34 .…”
Section: Discussionmentioning
confidence: 99%
“…However, direct measurement of the capillary-level GBCA concentration changes are not feasible due to the limited spatial resolution in MRI. Thus, we propose to utilize a deep learning network to predict the CIF that is local to a given patch of the tissue contrast dynamics, as demonstrated the feasibility with breast DCE-MRI data recently ( Bae et al, 2022 ). To model the vascular transport from the upstream artery to the capillary, we adopted two different pharmacokinetic models with different vascular transport designs.…”
Section: Methodsmentioning
confidence: 99%
“…We also conducted another study to overcome the challenges associated with the uncertainty in the AIF selection. We utilized the power of deep learning networks to automatically estimate the local capillary input function at the voxel-level for pharmacokinetic model analyses from the tissue contrast enhancement data ( Bae et al, 2022 ). In this study, we trained a network to predict the local capillary-level input function (CIF) for a given patch of the tissue contrast dynamics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation